Emulation of the Space Robotics System on Earth - Ten, Seng Teik (2001)
Present and future, without the sophisticated and highly automated mechanisms, it is impossible to fulfil the humanity's destiny in space. Thus to determine the success of ambitious space missions of the future, the humans and space robots have to form an excellent integrated team. Generally space robotic systems are designed, developed and operated to assist or replace humans in accomplishing tasks that are dangerous, costly or simply impossible for humans. The nature and operation of space systems are totally different from on earth such as zero gravity environments, have made the modifications of design and usage of robotics in space very important. This research comprises an analytical and experimental study of space robot locomotion. The main objective of this research work is to build a test-bed for space robot emulation that operates in the "zero gravity" situation. To experimentally study the locomotion of space robot in the laboratory, one has to create a "zero gravity" or "less gravity" environment. In order to perform simulations of partial or micro gravity environments on earth requires some method of compensation for the earth's gravitational field. To achieve this, gravity-less 2 Degrees-Of-Freedom robot with an unique instrumental arrangement was considered to compensate the gravity force. The space robot kinematics and dynamics formulations are studied, especially the Denavit-Hartenberg CD-H) parameters and Newton-Euler formulation. The feedbacks of the robot's arms are detected by encoders at the servomotors and transducers around the robot and sent to the computer through PC interface card. The space robot dynamic algorithms were tested in simulation and as well as in practical. The data especially the torque values, the joint positions and angular velocities of the robot's arm in the "zero gravity" environment as well as with gravitational effect were taken from the experimental and simulation. The simulation comprises the combination of mechanical simulation and virtual prototyping software, Mechanical Desktop and MSC Working Model. The graphs were plotted from data by using Excel. The Mathematical software package, Mathematica is used to derive the equations of motion. Finally all the trend graphs were plotted using Excel. The results were compared and analyzed with derived equations to prove that the "zero gravity" condition is achieved. Moreover this instrumental setup for emulation of space robot system can be used for various algorithms study based on robotics, control and other areas.